2019
DOI: 10.1016/j.jid.2018.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Th1 and Th17 Immune Responses Act Complementarily to Optimally Control Superficial Dermatophytosis

Abstract: Dermatophytoses are among the most common fungal infections worldwide but little is known about the immune response in them. By comparing Trichophyton benhamiae acute superficial dermatophytosis in WT and Rag2 mice, we showed that TCR-mediated immunity is critical for fungal clearance and clinical recovery. In WT mice, CD4+ T-cells isolated from the skin-draining lymph nodes exhibit both Th1 and Th17 differentiation during infection, with regard to produced cytokines or mRNA levels of transcription factors. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 78 publications
(84 reference statements)
5
52
0
2
Order By: Relevance
“…A similar protective role for Th17 has been demonstrated against the dermatophyte Trichophyton benhamiae [88]. While this most recent study confirmed the critical role of Th17 cells in protection from dermatophytosis, it reported a synergistic instead of an antagonistic role of IL-17- and IFN-γ-producing T cells to facilitate optimal fungal clearance [88]. The discrepancy between the two studies may be explained by differences in the two fungal genera, the mouse background and microbial status and/or details in the experimental protocol including the preparation of the mice for infection.…”
Section: Il-17 In Antifungal Immunity Beyond Candidasupporting
confidence: 54%
See 1 more Smart Citation
“…A similar protective role for Th17 has been demonstrated against the dermatophyte Trichophyton benhamiae [88]. While this most recent study confirmed the critical role of Th17 cells in protection from dermatophytosis, it reported a synergistic instead of an antagonistic role of IL-17- and IFN-γ-producing T cells to facilitate optimal fungal clearance [88]. The discrepancy between the two studies may be explained by differences in the two fungal genera, the mouse background and microbial status and/or details in the experimental protocol including the preparation of the mice for infection.…”
Section: Il-17 In Antifungal Immunity Beyond Candidasupporting
confidence: 54%
“…Analyzing the host response to dermatophytes in IL-17-deficient animals revealed that IL-17 not only limits dermatophyte growth on the skin, but also antagonizes a non-protective Th1 response against the fungus, which in the absence of IL-17 resulted in excessive skin inflammation and fungal overgrowth [87]. A similar protective role for Th17 has been demonstrated against the dermatophyte Trichophyton benhamiae [88]. While this most recent study confirmed the critical role of Th17 cells in protection from dermatophytosis, it reported a synergistic instead of an antagonistic role of IL-17- and IFN-γ-producing T cells to facilitate optimal fungal clearance [88].…”
Section: Il-17 In Antifungal Immunity Beyond Candidamentioning
confidence: 98%
“…Regarding the first possibility, it has been described that T. rubrum releases a variety of molecules, including proteases 30-32 , that can interact with host cells and eventually lead to down regulation of the expression of surface markers such as CD1a in LCs, thereby interfering with their function. In our second hypothesis, activated skin APCs migrate to regional lymph nodes to induce adaptive immune responses, but the systemic cellular immune response of dermatophytosis patients shows a tendency towards a non-protective, pathology-inducing, Th-2 13,33,34 response, even though their LCs are able to produce pro-inflammatory mediators, IL-12 included, locally 35 . Thus, we hypothesize that T. rubrum (or its products)-mediated activation and migration of LCs from the epidermis would not necessarily result in better in situ protective responses.…”
Section: Discussionmentioning
confidence: 87%
“…Recently, several reports described severe and occasionally life-threatening invasive disease (deep dermatophytosis) associated to genetic mutations in the innate immunity-associated molecule CARD9 6,8,11 , highlighting the need to better understand the immune response in this infection. Recently, studies in animal models of dermatophytosis have demonstrated that Th17 and eventually Th1 immune responses were essential to the optimal control of this fungal infection 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Baltazar et al (112) reported that IL-12p40 KO mice (lacking common b-subunit of IL-12 and IL-23 and thus, with impaired IL-17 and IFN-g signaling) or IFN-g KO mice were able to control T. rubrum infection after 14 days, but showed an increased fungal burden in the first week compared to infected WT mice. Eventually, as described for the M. canis model (51), deep dermatophytosis was not observed in the absence of IL-17 and IFN-g in neither infection models (112,120), suggesting that several immune pathways must be compromised to establish invasive dermatophytosis. The effector mechanisms of IFN-g remains unclear but Verma and Gaffen (121) hypothesized that, as observed in Candida skin infection, IFN-g may contribute to T. benhamiae destruction and expulsion by activating the fibrinolytic system in the epidermal abscess (122) or promoting M1 macrophages at a later infection stage ( Figure 2).…”
Section: Type 1 (Ifn-g-mediated) Immunitymentioning
confidence: 81%